STUDYING THE PATIENTS' LOYALTY AND SATISFACTION STATUS REFERRED TO MEDICAL SCIENCES HOSPITALS OF YASOOJ - ZARIN, ZYNAB; OSTVAR, RAHIM; ASL, IRAVAN MASOUDI (International Journal of Clinical and Biomedical Research, 2016)
The Goal of present research namely 'Studying the patients' loyalty and satisfaction status referred to Medical Sciences hospitals of Yasooj is given to the results obtained from the analyses done can reduce the patients' dissatisfaction resulting from the following mentioned issues and increases their loyalty to the hospitals. This research includes 7 hypotheses and the method of gathering data is questionnaire. The research questionnaire consists of two parts: the first part is related to the patientsÌ’satisfaction and the second on measures their loyalty. To analyze data, the software SPSS was used. The studies performed that there is a significant relationship between the patients satisfaction and loyalty and the service status. Also, there is a significant relationship between the remaining hypotheses including the patients age and gender and the service status. There is a significant relationship between the patients age and their gender. There is also a significant relationship between the patients' loyalty and satisfaction with their residency.